ANALISIS PENGHITUNGAN PROYEKSI BELANJA OPERASIONAL KEMENTERIAN NEGARA DAN LEMBAGA UNTUK PENYUSUNAN PAGU INDIKATIF - Renosa Tosca Zamaro (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2018)
In Directorate General of Budget, two methods are used in formulating forecast of operational spending in Line Ministries to produce Indicative Budget. The first method uses the realization of line ministries operational spending two years prior to the planned fiscal year as the basis for the forecast. Whereas in the second method, the operational spending allocation is forecasted based on budget allocation in the APBN one year prior to the planned fiscal year. This study aims to find out a better calculation model in operational spending forecasting in line ministries. Two methods used in Directorate General of Budget in forecasting operational spending is analyzed using multiple linear regression using panel data. The analysis conducted on 71 Line Ministies during five years period, 2011 to 2015. The result of the study indicates that the method to forecast operational spending allocation using budget allocation in the APBN one year prior to the planned fiscal year is statistically better.